TANGGUNG JAWAB BADAN HUKUM PADA TINDAK PIDANA HUMAN TRAFFICKING BERDASARKAN UNITED NATION CONVENTION AGAINST TRANSNATIONAL ORGANIZED CRIME TERHADAP NEGARA INDONESIA DAN MALAYSIA - Asri Qhornelis Putri; Zulfikar Jayakusuma; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Countries around the world are increasingly facing crimes that cross nationalborders, one of which is human trafficking. These crimes threaten and force countriesin the world and the United Nations to regulate a rule of law that can prevent andprosecute these crimes. In 2000, the Palermo Convention, known as the UnitedNations Convention Against Transnational Organized Crime (UNTOC), was born.This type of research is normative legal research, namely legal researchcarried out by examining library materials in the form of binding legal rules andsecondary data such as other literature related to this research through a statuteapproach and comparative approach. This research is a qualitative data analysis inwhich descriptions are made of legal data that has been collected logically andsystematically. This research uses dualisme theory and functional dictatorshiptheory.The result of this research is that Member States have an obligation toincorporate legal entities into their national law. The mandate of UNTOC hasimplications for the laws of Indonesia and Malaysia as Member States. Thatimplication is dualism in applying international law through legal transformation sothat international law can apply in the laws of Indonesia and Malaysia. The rules arecreated through policies, so that Law No. 21 of 2007 on the Eradication of the Crimeof Trafficking in Persons in Indonesia and the Anti-Trafficking in Persons Act 670 of2007 in Malaysia were born. These acts regulate legal entities (corporations) aslegal subjects to prevent, prosecute, and punish corporations for committing thecrime of trafficking in persons.Keywords: Legal Person, Human Trafficking, UNTOC